Mitigating irrigation-induced soil erosion and enhancing soil ecosystem services on sloping lands using zig-zag furrow irrigation in cotton production - Tadjiev, Sunnat; Isashov, Anvarjon; Ashirov, Yusuf; Djumanazarova, Altingul; Butayarov, Abdukadir; Sarimsakov, Maksudkhon; Isaev, Sabirjan; Khojasov, Allamurat; Zokirova, Sanoat; Tadjieva, Madina; Narzullaev, Jamshid; Malikov, Elyor; et al. (Frontiers in Agronomy, 2026)
IntroductionIrrigation-induced soil erosion poses a serious challenge to sustainable agriculture on sloping lands in arid and semi-arid regions. Conventional straight furrow irrigation often accelerates soil and nutrient losses and reduces water use efficiency.MethodsField experiments were conducted during the 2019–2021 growing seasons in the Piskent district of the Tashkent region, Uzbekistan, on meadow-sierozem soils with slope gradients of 1.5°, 2.5°, and 3.5°. A randomized complete block design was used to compare zig-zag furrow irrigation with conventional straight furrow irrigation. Measurements included flow characteristics, soil erosion, nutrient losses, irrigation water use, water use efficiency, and seed cotton yield.ResultsZig-zag furrow irrigation significantly reduced flow velocity and soil erosion, resulting in a 4–5-fold decrease in soil loss compared to conventional furrows. Seasonal irrigation water use decreased by 15–20%, while nitrogen and phosphorus losses were reduced by 35–40%. Water use efficiency improved from 1902 m³ t⁻¹ to 1426 m³ t⁻¹, and seed cotton yield increased by 0.32–0.43 t ha⁻¹.DiscussionThe results demonstrate that modifying furrow geometry through a zig-zag configuration enhances regulating ecosystem services related to soil conservation, water regulation, and nutrient retention. This low-cost and scalable approach offers a practical solution for improving irrigation sustainability and crop productivity on erosion-prone sloping lands.